Not hedon not famous - Chusnul Rofiah; Andi Styawan (Enrichment : Journal of Management, 2023)
The increase in internet users and the development of e-commerce in Indonesia have influenced consumer buying behavior. One of the unique characteristics of Indonesian consumers is that they tend not to plan. Students tend to have a high sense of curiosity, so students often want to try new things that will shape their lifestyle. This study aims to understand and describe the dynamics of the hedonistic lifestyle in STIE PGRI Dewantara Jombang students. The method used in data collection is interviews, where there is a two-way interaction between the researcher and the research subject, to obtain information that is following the research focus. In this study, the determination of informants was carried out using a purposive technique, in which informants were selected based on certain considerations and predetermined criteria. The results of the study show that the hedonistic lifestyle of STIE PGRI Dewantara Jombang students involves individual views that prioritize personal pleasure. Activities such as shopping, walking, watching movies, spending time at the mall, using a private car when going to campus, owning gadgets priced above 5 million rupiahs, and wearing trendy clothes according to current trends in the campus environment.